The prognostic influence of histological subtypes of micropapillary tumors on patients with lung adenocarcinoma ≤ 2 cm - Xu, Liangdong; Zhou, Hangcheng; Wang, Gaoxiang; Huang, Zhining; Xiong, Ran; Sun, Xiaohui; Wu, Mingsheng; Li, Tian; Xie, Mingran (Frontiers in Oncology, 2022)
Objective: This study aimed to explore the value of micropapillary histological subtypes in predicting the specific surgical specificity and lymph node metastasis prognosis of early lung adenocarcinoma. Methods: A total of 390 patients with non-small-cell lung cancer were included who underwent surgery . The data were analysed with SPSS 26.0 statistical software, and the clinicopathological data of the two groups were compared with the chi-square test. The survival rate was calculated by the Kaplan–Meier method, and the difference in survival rate between groups was analysed by the log-rank test. Multivariate survival analysis was performed using the Cox model. Results: Univariate analysis of the clinicopathological data of the patients showed that the micropapillary histological subtype was significantly associated with the survival rate of patients (p=0.007). The clinicopathological data of the patients were substituted into the Cox model for multivariate analysis, and the micropapillary histological subtype was an independent prognostic factor affecting the survival rate (p=0.009).The average survival time of Group A（micronipple composition > 5%）was 66.7 months; the 1-year, 3-year, and 5-year survival rates were 98.8%, 93.0%, and 80.9%, respectively.The survival of the lobectomy group was better than that of the sublobectomy group and the survival of patients with systematic dissection was better than the limited lymph node dissection.The average survival time of Group B(micronipple composition ≤ 5%) was 70.5 months; the 1-year, 3-year, and 5-year survival rates were 99.3%, 95.4%, and 90.6%, respectively. There was no difference in the survival rate between the lobectomy group and sublobectomy group, and there was also no difference in survival between systematic lymph node dissection and limited lymph node dissection,The survival rate of Group B was significantly better than the Group A. Conclusion:The micropapillary histological component is an independent risk factor after surgery in patients with ≤2 cm lung adenocarcinoma. When the proportion of micropapillary components is different, the prognosis is different when different surgical methods and lymph node dissections are performed. Lobectomy and systematic lymph node dissection are recommended for patients with a micropapillary histological composition >5%; sublobar resection and limited lymph node dissection are recommended for patients with a micropapillary histological composition ≤5%.